Airway Challenges and Solutions in Tracheal Reconstruction Surgery: A Case Report of Severe Post-Tracheostomy Stenosis - Adiptya Cahya Mahendra; Purwoko (HM Publisher, 2025)
Introduction: Tracheal stenosis, a narrowing of the trachea, can pose significant challenges for airway management, especially during tracheal reconstruction surgery. This case report presents the successful management of a complex airway in a patient with severe post-tracheostomy tracheal stenosis. Case presentation: A 28-year-old male presented with severe tracheal stenosis following a tracheostomy two years prior. The patient was scheduled for tracheal reconstruction surgery. Intraoperatively, the initial challenge was the poor patency of the existing tracheostomy tube, necessitating its replacement with an uncuffed endotracheal tube (ETT). Further airway challenges arose during the stenting procedure, requiring innovative solutions to maintain airway patency while facilitating surgical access. Conclusion: This case highlights the critical role of flexible and innovative airway management techniques in tracheal reconstruction surgery. Meticulous planning, close collaboration between the surgical and anesthesia teams, and the ability to adapt to unexpected intraoperative challenges are essential for successful outcomes in these complex cases.